Wire and extended ladder model predict THz oscillations in DNA monomers, dimers and trimers. (12th October 2016) - Lambropoulos, K; Kaklamanis, K; Morphis, A; Tassi, M; Lopp, R; Georgiadis, G; Theodorakou, M; Chatzieleftheriou, M; Simserides, C
Abstract: We call monomer a B-DNA base pair and study, analytically and numerically, electron or hole oscillations in monomers, dimers and trimers . We employ two tight binding (TB) approaches: (I) at the base-pair level, using the on-site energies of the base pairs and the hopping parameters between successive base pairs i.e. a wire model, and (II) at the single-base level, using the on-site energies of the bases and the hopping parameters between neighbouring bases, specifically between (a) two successive bases in the same strand, (b) complementary bases that define a base pair, and (c) diagonally located bases of successive base pairs, i.e. an extended ladder model since it also includes the diagonal hoppings (c). For monomers, with TB II, we predict periodic carrier oscillations with frequency f ≈ 50 –550 THz. For dimers, with TB I, we predict periodic carrier oscillations with f ≈ 0.25 –100 THz. For trimers made of identical monomers, with TB I, we predict periodic carrier oscillations with f ≈ 0.5 –33 THz. In other cases, either with TB I or TB II, the oscillations may be not strictly periodic, but Fourier analysis shows similar frequency content. For dimers and trimers, TB I and TB II are successfully compared giving complementary aspects of the oscillations.